Possible Involvement of Central Nervous System in COVID-19 and Sequence Variability of SARS-CoV-2 Revealed in Autopsy Tissue Samples: A Case Report - Lis Høy Marbjerg; Christina Jacobsen; Jannik Fonager; Claus Bøgelund; Morten Rasmussen; Anders Fomsgaard; Jytte Banner; Veronika Vorobieva Solholm Jensen (SAGE Publishing, 2021)
The case presented here illustrates that interdisciplinary teamwork can be essential for the understanding of the COVID-19 disease presentation and enlightening of the pathophysiology. A 60-year-old woman without any comorbidities, apart from overweight, was found dead in her apartment after 14 days of home isolation due to suspicion of COVID-19. A forensic autopsy was performed. This revealed severely condensed, almost airless, firm lungs, and the cause of death was severe acute respiratory distress syndrome-associated with COVID-19 (SARS-CoV-2). In addition, SARS-CoV-2 was detected with reverse transcription polymerase chain reaction (RT-PCR) in cerebrospinal fluid, lung tissue, and tracheal sample and specific antibodies for SARS-CoV-2 were detected in cerebrospinal fluid and serum. Subsequent sequencing of the SARS-CoV-2 virus showed variation in nucleotides at 3 sites between SARS-CoV-2 isolates recovered from the tracheal sample, cerebrospinal fluid, and tissues from both lungs, and phylogenetic analysis revealed that the spinal fluid sample differed the most from the other 3 samples. This case supports the hypothesis that SARS-CoV-2 may be neuroinvasive and cause central nervous system infection.